The Cost of Regulating Effort: Reward and Difficulty Cues With Longer Prediction Horizons Have a Stronger Impact on Performance - Nanne Kukkonen; Senne Braem; Jens Allaert; Joshua O. Eayrs; Nicoleta Prutean; S. Tabitha Steendam; C. Nico Boehler; Jan R. Wiersema; Wim Notebaert; Ruth M. Krebs (Journal of Cognition)
Many theories on cognitive effort start from the assumption that cognitive effort can be expended at will, and flexibly up- or down-regulated depending on expected task demand and rewards. However, while effort regulation has been investigated across a wide range of incentive conditions, few investigated the cost of effort regulation itself. Across four experiments, we studied the effects of reward expectancy and task difficulty on effort expenditure in a perceptual decision-making task (random-dot-motion) and a cognitive control task (colour-naming Stroop), and within each task comparted cues between short (cueing the next trial) and long (cueing the next six trials) prediction horizons. We found that participants used the cue information only when it was valid for multiple trials in a row. In the random-dot-motion task, a high reward expectancy resulted in better accuracy, especially in easy trials, but only with long prediction horizon. Similarly, in the Stroop task, the reward facilitation of reaction time was only observed after reward cues with a long prediction horizon. Together, our results indicate that people experience a cost to effort regulation, and that lower adjustment frequency can compensate for this cost.